Preferential binding of SBD from Arabidopsis thaliana SSIII to polysaccharides: Study of amino acid residues involved - Valdez, Hugo Alberto (2011)
SS III (SSIII) has been reported as playing a regulatory role in the synthesis of transientstarch. SSIII from Arabidopsis thaliana contains 1025 amino acid residues and has an Nterminaltransit peptide for chloroplast localization followed by three in tandem starch-bindingdomains (SBDs D1, D2, and D3, residues 22-591). Its C-terminal catalytic domain (residues592–1025) is similar to bacterial glycogen synthase. Binding studies to raw starch and itsindividual components, AM or AP show that the SBD region binds preferentially to AM, andthat the D1 domain is mainly responsible for this selective binding. The D2 domain containstwo binding sites which include amino acid residues Y394 (binding site 1) and W366 (bindingsite 2) acting cooperatively with the D1 domain in the binding process while G335 and W340have a minor role. In addition, mutations in these residues also affect the kinetic parametersfor the polyssacharide substrate of SSIII.